Nature-Based Physical Activity in Pictures: A Photovoice Unit in (and Beyond) Physical and Health Education (LEARNing Landscapes, 2024)
Experts in public health and education alike have long advocated for the engagement of youth in nature to foster movement, human–nature connectedness, and mental wellbeing. Physical and health education teachers in school-based programs continue to find a variety of ways to help their students be physically active in the natural environment due to the plethora of positive benefits. This paper describes a unit entitled Nature-Based Physical Activity in Pictures that utilized Photovoice to engage youth and foster human–nature connectedness.
Keywords: human-nature connectedness; lifetime physical activity; adolescent mental wellbeing